Opportunities and Empowerment of Rural Women Entrepreneurs with Skills of ICT - GEETHA,; LAKSHMI. A, (International Journal of Psychosocial Rehabilitation, 2020)
Women entrepreneurs are important contributors to Indian economy. Women’s economic empowerment is critical to achieving gender equality and sustainable development. Women are key contributors to economies as producers of food, managers of natural resources and as entrepreneurs and employees. Additionally, women are the main providers of unpaid care and domestic work - globally, Information and Communication Technology (ICT) can help to overcome some of them, and there are also business opportunities in the ICT sector itself. In today’s competitive world the survival of many business organizations are largely depending on the effective and efficient use of ICTs. ICT tools are helping women entrepreneurs with unique and vast opportunities to empower themselves in multifarious way. This study examined the veritable roles of ICT in empowering rural women. the roles of ICTs in rural women empowerment and constraints to the use of ICT devices by the respondents.